The Penitentiary Acts and the rules and regulations for the government of the Newfoundland Penitentiary - Newfoundland (Printed at the Evening Telegram Office, 1891)
This item contains several Acts relating to the Newfoundland Penitentiary as well as its formal regulations. Together these cover all aspects of prisoner treatment and prison staffing, including guidelines for feeding, punishment and commutation of sentence. -- Tipped in between p.10-11: "Certified copy of minutes of the Honourable Executive Council .", Nov. 8. (1 leaf 28 cm.). This sheet adds some additional information to the printed Acts.